HCF-Web: um sistema web para o Herbário HCF da UTFPR-CM - Sangali, Elaine Cecilio (2019)
The Federal Center Herbarium (HCF), Federal University of Paraná - Campus Campo Mourão (UTFPR-CM), uses a system that stores the data observed in the collected plant samples. The Herbarium 1.0 system was implemented in 2006 to replace the manual record process of the plants collected. With the collection growth and the herbarium expansion, the demand for new features increased, including the ability to export data to the Darwin Core model. This work focus on the implementation of a new system using web technologies to meet the recent demands of the HCF Herbarium. Among them, the development of a script able to convert the data from HCF to Darwin Core model to allow the data use by the Brazilian Biodiversity Information System (SIBBr). The current database model was also refactored during the requirement analysis phase. Finally, a new online system was implemented, the HCF-Web, which allowed the repair of issues present in the current system, such as, problems visualizing text data, deprecated functions, incorrect data modeling and single-user access. The results were the improvement in the data exportation and intercommunication of the herbarium eith other systems through the database standardization; controlled multiple user access; and finally, the technological update of the system through the implementation of a system using web technologies.